Reverse oxygen spillover triggered by CO adsorption on Sn-doped Pt/TiO2 for low-temperature CO oxidation - Chen, Jianjun; Xiong, Shangchao; Liu, Haiyan; Shi, Jianqiang; Mi, Jinxing; Liu, Hao; Gong, Zhengjun; Oliviero, Laetitia; Maugé, Françoise; Li, Junhua (Nature communications, 2023)
The spillover of oxygen species is fundamentally important in redox reactions, but the spillover mechanism has been less understood compared to that of hydrogen spillover. Herein Sn is doped into TiO 2 to activate low-temperature (<100 °C) reverse oxygen spillover in Pt/TiO 2 catalyst, leading to CO oxidation activity much higher than that of most oxide-supported Pt catalysts. A combination of near-ambient-pressure X-ray photoelectron spectroscopy, in situ Raman/Infrared spectroscopies, and ab initio molecular dynamics simulations reveal that the reverse oxygen spillover is triggered by CO adsorption at Pt 2+ sites, followed by bond cleavage of Ti-O-Sn moieties nearby and the appearance of Pt 4+ species. The O in the catalytically indispensable Pt-O species is energetically more favourable to be originated from Ti-O-Sn. This work clearly depicts the interfacial chemistry of reverse oxygen spillover that is triggered by CO adsorption, and the understanding is helpful for the design of platinum/titania catalysts suitable for reactions of various reactants. Reverse O spillover has opened new opportunities in improving the catalytic activity and selectivity in various reactions. Herein Sn is doped into TiO2 to activate low-temperature (<100 °C) reverse oxygen spillover in Pt/TiO2 catalyst, leading to enhanced CO oxidation activity.